Cook it up : bold moves for family foods - Guarnaschelli, Alex, 1969-; Clark, Ava (Clarkson Potter/Publishers, 2023)
"Through seventy-five witty and informative recipes, Alex and Ava share a repertoire of dishes that define their modern family meals: bold flavored, comforting, satisfying, and always supremely delicious. Side by side, they cook their way through family favorites like Alex's renowned cookbook editor/mom's famous Blueberry Pie and Nanny Ida's Crisp Potato Latkes and offer sound cooking advice for achieving the fluffiest frittatas (add water, never milk) and how to properly season and mix a chicken meatball mixture so the meatballs stay juicy (spread the mixture up around the sides of the bowl and then season). There's even a bonus recipe for dog biscuits, inspired by Alex and Ava's family dog, Leon!"--